Relationship between oil price and white precious metals return: A new evidence from quantile-on-quantile regression - Imtiaz Arif; Lubna Khan; Khalid Mehmood Iraqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
The present study examines the effects of oil price on white precious metal returns by using quantile-on-quantile regression proposed by Sim and Zhou (2015). In this study, we mainly focus on the returns of three white precious metals, which include palladium, silver, and platinum. The study is conducted on the monthly data of crude oil price and white precious metals from the period of January 2000 to December 2016. We use QQR approach to capture the complete picture of the studied relationship. Unlike conventional techniques, QQR provides the comprehensive results of the variables at distinct quantiles. Similarly, the ARDL technique has also been used. Results reveal that the change in global oil price increases the returns of platinum and palladium. Whereas, an insignificant relationship has been found between the oil prices and silver returns. Results indicate that palladium and platinum both precious metals act as a safe haven for investors. In contrast, change in oil prices will not lead to high silver returns. Therefore, investors need to be prudent while investing in silver. These results have important policy implications for policymakers and investors.
Keywords: 330; platinum; silver; palladium; quantile on quantile approach; oil price